2011
DOI: 10.1111/j.1365-2567.2011.03409.x
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of phenotypic and functional characteristics of CX3CR1‐expressing natural killer cells

Abstract: Summary We previously demonstrated a correlation between the frequency of CX3CR1‐expressing human natural killer (NK) cells and disease activity in multiple sclerosis and showed that CX3CR1high NK cells were more cytotoxic than their CX3CR1neg/low counterparts. Here we aimed to determine whether human NK cell fractions defined by CX3CR1 represent distinct subtypes. Phenotypic and functional NK cell analyses revealed that, distinct from CX3CR1high, CX3CR1neg/low NK cells expressed high amounts of type 2 cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 46 publications
5
74
0
Order By: Relevance
“…6 CX 3 CR1 is furthermore expressed by macrophage/ dendritic cell precursors, 7 various dendritic cell (DC) progenitors, a nonclassic CD8␣ ϩ DC subset, 8 and plasmacytoid DCs. Aside from the prominent expression in the mononuclear myeloid compartment, CX 3 CR1 receptor expression has been reported for an NK cell subset 3,9 and certain T-cell populations. 3,10,11 The in vivo expression pattern of the ligand CX 3 CL1 remains less well defined and controversial 12 but has been reported for neurons, 13 intestinal epithelium, 14 and inflamed endothelium.…”
Section: Introductionmentioning
confidence: 99%
“…6 CX 3 CR1 is furthermore expressed by macrophage/ dendritic cell precursors, 7 various dendritic cell (DC) progenitors, a nonclassic CD8␣ ϩ DC subset, 8 and plasmacytoid DCs. Aside from the prominent expression in the mononuclear myeloid compartment, CX 3 CR1 receptor expression has been reported for an NK cell subset 3,9 and certain T-cell populations. 3,10,11 The in vivo expression pattern of the ligand CX 3 CL1 remains less well defined and controversial 12 but has been reported for neurons, 13 intestinal epithelium, 14 and inflamed endothelium.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, further markers were shown to distinguish between different maturation subsets. We showed that CX3CR1 − NK cells were immature NK cells and that the chemokine receptor CX3CR1 may serve in combination with CD56, CD57, CD62L, and CD27 to define different steps of NK cell maturation (Hamann et al, 2011). The NK cell maturation and receptor expression profile is depicted in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a reduction of blood NK cells expressing CX3CR1 correlated with disease severity (54). Because CD56 bright NK cells were shown to be CX3CR1 2 in normal donors, it would be interesting to further look at the capacity of daclizumab to modulate CX3CR1 expression on NK cell subtypes (58). Manipulation of NK cells in animal models of EAE leads to contradictory results.…”
Section: Nk Cell Modifications Associated With Cns Disordersmentioning
confidence: 99%